The Effects of Alcohol Abstinence on BDNF, Ghrelin, and Leptin Secretions in Alcohol‐Dependent Patients with Glucose Intolerance. (13th September 2012) - Kim, JH; Kim, SJ; Lee, WY; Cheon, YH; Lee, SS; Ju, A; K, Min; Kim, DJ
Abstract : Background: Alcohol use affecting the risk of type 2 diabetes mellitus (T2DM) is poorly identified as well as the role of brain‐derived neurotrophic factor (BDNF), ghrelin, and leptin in alcohol dependence with T2DM. We tested the hypothesis that alcohol abstinence affects diabetes‐related factors and BDNF, ghrelin, and leptin secretions in alcohol‐dependent patients with glucose intolerance. Methods: A total of 64 male alcohol‐dependent patients were classified into normal glucose tolerance (NGT), pre‐diabetes mellitus (pre‐DM), and diabetes mellitus (DM) groups according to a 75‐g oral glucose tolerance test (OGTT). All participants got alcohol dependence rehabilitation treatment for 30 days, and then we compared changes in BDNF, ghrelin, and leptin between pre‐ and post‐alcohol abstinence. Results: After alcohol abstinence, both pre‐DM and DM groups had significantly decreased levels of fasting glucose. All 3 groups exhibited elevated ghrelin levels and reduced leptin levels, but BDNF levels were significantly increased only in the pre‐DM group. The pre‐DM group had large increases in BDNF and ghrelin levels compared with those of the NGT group. Moreover, decreases in homeostasis model assessment of insulin resistance (HOMA‐IR), fasting glucose, and leptin levels in the DM group were larger than those in the NGT group. Conclusions: Alcohol abstinence might influence diabetes‐related factors of alcohol‐dependent patients with glucose intolerance. Further, BDNF, ghrelin, and leptin differently affect this improvement, depending on the stage of DM. In the pre‐DM group, elevated BDNF and ghrelin levels are likely to influence insulin sensitivity, insulin resistance, and fasting glucose levels. Further, reduced leptin levels after abstinence might be related to improved glucose kinetics in patients with diabetes.